PERANAN AUDITOR INTERNAL DALAM MENINGKATKAN KINERJA MANAJEMEN - Wahyuningtyas, Cipryana -; Sarwono, Aris Eddy; Kristianto, Djoko - (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2014)
The purpose of this study was to determine the role of internal auditors in improving performance management (case study on service cooperative joint venture (KJUB) Puspetasari. Analysis showed that the role of internal auditors in improving management performance by managers around 302 and under range 98 is internal auditors a very important role. This can be seen from the results of the questionnaire obtained is that the role of internal auditors is very instrumental. overall the elements of the internal control system has implemented well, as evidenced by the existence of organizational structures that separate functional responsibilities explicitly, the authorization system and good recording, sound practices, and competent employees who have performed well. so it can be concluded that the role of internal auditors in improving the performance of the Management is very involved. it can be seen from the results of the questionnaires and field analysis of the elements internal control systems Service Cooperative Joint Venture Puspetasari have done well. Keywords: Internal Auditor, Performance Management, Internal Control System